2021
DOI: 10.1177/13591045211044743
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to mental health admissions for children and adolescents experiencing mental health crises: A systematic review of the literature

Abstract: Background: Many children and young people (CYP) presenting with mental health crises are admitted to hospital due to concerns around illness severity and risk. Whilst inpatient admissions have an important role for such children, there are a number of burdens associated with them, and safe avoidance of admissions is favourable. We systematically reviewed the literature for studies of interventions reported as alternatives to a hospital admission in CYP presenting with mental health crises, in any inpatient se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Innovations for integrated care show promising evidence for reducing the rate of emergency admissions to an acute ward, the LOS in both the emergency department and inpatient setting, and the rehospitalisation rate after discharge. Thus, integrated care not only improves health outcomes [ 17 , 18 ] and effectively reduces psychiatric hospitalisation [ 19 ]—this review adds that signposting to psychological interventions also reduces emergency readmissions in paediatric emergency settings too. Whilst there is sometimes no alternative to hospitalisation for medical emergencies [ 16 , 17 ], integrating psychiatric care into emergency services helps to triage effectively, intervene earlier, and signpost to therapeutic support, reducing lengthy and repeat hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Innovations for integrated care show promising evidence for reducing the rate of emergency admissions to an acute ward, the LOS in both the emergency department and inpatient setting, and the rehospitalisation rate after discharge. Thus, integrated care not only improves health outcomes [ 17 , 18 ] and effectively reduces psychiatric hospitalisation [ 19 ]—this review adds that signposting to psychological interventions also reduces emergency readmissions in paediatric emergency settings too. Whilst there is sometimes no alternative to hospitalisation for medical emergencies [ 16 , 17 ], integrating psychiatric care into emergency services helps to triage effectively, intervene earlier, and signpost to therapeutic support, reducing lengthy and repeat hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of therapeutic modalities on improving health outcomes is well documented. [ 17 ] For example, integrating family-based therapy within acute hospitalisation has been provided in medical emergencies that are accompanied by a comorbid mental illness—particularly eating disorders and suicide attempts. This is known as partial hospitalisation, which involves transferring the patient from an inpatient ward to outpatient family-based therapy once medical stabilisation is complete; aimed at reducing the degree of institutionalisation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental health disorders, especially those of greater severity, negatively influence the adolescent's overall quality of life. If left untreated, mental health disorders can result in several While inpatient settings are instrumental in stabilizing severe mental health disturbances, they may also carry burden [22], such as being costly for the healthcare system [23], having limited capacity [24] and requiring disconnection from family, friends, education and employment. Thus, safe and effective alternatives to inpatient admissions in community settings are favoured [22].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, inpatient admissions were reserved for comprehensive evaluations [9], the stabilization of symptoms and the reduction of imminent risk [10] among individuals with severe behavioural or emotional disturbances [11][12][13]. However, recent studies have suggested an increase in both emergency room visits and hospitalizations that are not thought to have occurred solely due to medically serious suicide attempts [14] or heightened mental health conditions [15,16]. The etiology of mental health conditions is complex and is associated with a number of factors, including but not limited to, individual characteristics (e.g., sex) [17,18], interpersonal relationships [19] and traumatic life events (e.g., physical assault, sexual abuse) [20].…”
mentioning
confidence: 99%